Pengaruh Pemberian Ekstrak Daun Salam (Eugenia Polyantha) Terhadap Kadar Asam Urat pada Pasien Prolanis di Klinik Iman - Palupi Ayundari; Shahrul Rahman (Indonesian Journal Publisher, 2026)
The objective of this study was to examine the effect of bay leaf extract on uric acid levels in patients with hyperuricemia. The study used a quantitative approach with a non equivalent control group experimental design. Participants were divided into an experimental group and a control group. The experimental group received bay leaf extract, while the control group received no intervention. Uric acid levels were measured before and after the intervention. Data analysis used the Paired Sample T-Test to compare uric acid levels before and after treatment in the experimental group. The results showed a significant reduction in uric acid levels after administration of bay leaf extract. The p value was 0.002, which is lower than 0.05, indicating a statistically significant difference. These findings demonstrate that bay leaf extract has a significant effect on reducing blood uric acid levels in patients with hyperuricemia at Klinik Iman. The study provides empirical evidence supporting the potential use of bay leaf extract as an alternative herbal therapy for managing hyperuricemia.